'Beautiful Tasmania': environmental consciousness in John Watt Beattie's romantic wilderness. Issue 1 (2nd January 2017) - Hore, Jarrod
Abstract: This article explores an orientation to nature in fin de siècle Tasmania. I argue that this orientation drew upon a romantic tradition to support a sympathetic environmental consciousness among settlers. This consciousness was apprehended through the public work of wilderness photographers like John Watt Beattie. The explication of such a culture of sympathetic environmental consciousness through the archive of Beattie himself offers an alternative to existing accounts of the development of conservation ideology and environmentalism in the Australian colonies in the late nineteenth century.